2014
DOI: 10.3390/soc4020265
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Racial Interactions during College: A Longitudinal Study of Four Forms of Interracial Interactions among Elite White College Students

Abstract: Abstract:College and universities present distinct opportunities to interact across racial and ethnic lines that may influence people's prejudice toward different groups. This study examines the influence of four forms of cross-race interaction on traditional and modern forms of racial prejudice among white college students at 28 of the most selective colleges and universities in the US. This study finds that, although white students' level of racial prejudice declines over four years, interracial contact duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Black students are also disproportionately more likely to leave their degree programme prior to completion (Higher Education Statistics Agency [HESA], 2018). These patterns of racial inequality are common across Western higher education systems including the US, Australia, Belgium, and France (e.g., Byrd, 2014; Colak, Van Praag, & Nicaies, 2020; Ichou & van Zanten, 2019; Pitman, Roberts, Bennett, & Richardson, 2019). Recently, student campaigns, media commentary, and academic voices have insisted that our attention shifts from encouraging underrepresented groups through the door, to addressing the Whiteness of our institutions that signals non‐belonging and may compromise Black students' ability to thrive (National Union of Students, 2011; Richardson, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Black students are also disproportionately more likely to leave their degree programme prior to completion (Higher Education Statistics Agency [HESA], 2018). These patterns of racial inequality are common across Western higher education systems including the US, Australia, Belgium, and France (e.g., Byrd, 2014; Colak, Van Praag, & Nicaies, 2020; Ichou & van Zanten, 2019; Pitman, Roberts, Bennett, & Richardson, 2019). Recently, student campaigns, media commentary, and academic voices have insisted that our attention shifts from encouraging underrepresented groups through the door, to addressing the Whiteness of our institutions that signals non‐belonging and may compromise Black students' ability to thrive (National Union of Students, 2011; Richardson, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…White experiences in White-minority religious organizations reveal similar assumptions about disproportionate influence, normative moral goodness, and extreme defensiveness when challenged or made aware of racial realities (Christerson et al 2005;Edwards 2008). These patterns may explain why studies show interracial relationships often do not produce white antiracist frames among White Americans (Byrd 2014;Cobb et al 2015;Edwards 2008;Perry 2017;Twine 2010). In the situation of White parents of Black adopted children, the perception of racial scrutiny provides yet another complicating factor-that of White parents being made aware that their Black children are under surveillance, and by extension, they are also being scrutinized.…”
Section: White Normativity Perceptions Of Victimization and White Exp...mentioning
confidence: 99%
“…Consequently, perceived prejudice has been acknowledged as a key factor affecting individuals' emotions, feelings, and attitudes toward outgroup members. Moreover, the outcome of numerous studies addressing the prejudice-behavior link in a variety of situations points to prejudice that can strongly influence individuals' beliefs, attitudes, and actual behavior (Byrd, 2014;Crisp & Turner, 2009;Dovidio et al, 2002;Fujimoto & Hartel, 2004;Knowles, Lowery, & Shaumberg, 2010). For example, a study by Greenwald, Smith, Sriram, Bar-Anan, and Nosek (2009) found prejudice predicts voting behavior, including for the 2008 elections, the first time in which an African American (Barack Obama) was elected president of the United States.…”
Section: Literature Reviewmentioning
confidence: 99%